Weak tides during Cryogenian glaciations - J. A. Mattias Green (Nature Portfolio, 2020)
How and why the ‘Snowball Earth’ occurred during the Cryogenian period is debated. Here, the authors show that the cryogenian ocean hosted diminished tidal amplitudes and associated energy dissipation rates, reaching 10-50% of today’s rates thus perhaps contributing to prolonged glaciations.